Effect of Material on Lathe Rotation at HSS (High Speed Steel) M42 Tool Cutting Tool Wear Level - Alfian Achmad Nuryanto; Yasinta Sindy Pramesti (Publikasi Indonesia, 2024)
In an era where science and technology are rapidly developing, in the era of globalization it opens a wide door for every individual to embrace change. Human resources, being the pulse that pumps industrial life, must be proficient in mastering science and technology, being able to apply it in every step of the industry, and steel has become an important milestone in various sectors, from building construction to machine components. However, behind the glitter of this civilization, technical processes such as turning the HSS M42 chisel face its own challenges. At certain rpm cycles, the tool experiences an erratic level of wear, as evidenced by the difference between the initial and final weights as well as the difference in the initial and final lengths. In the HSS M42 tool turning attempt, the HSS M42 1200 type tool with a size of 3/8x3/8x4